2015
DOI: 10.1016/j.vetpar.2015.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Orientation behaviour of Culicoides obsoletus (Diptera: Ceratopogonidae), a relevant virus vector in northern Europe, toward host-associated odorant cues

Abstract: a b s t r a c tSome Culicoides biting midge species (Diptera: Ceratopogonidae) are biological virus vectors worldwide and have recently been associated with outbreaks of important epizootic diseases such as bluetongue and Schmallenberg in northern Europe. These diseases, which affect domestic and wild ruminants, have caused considerable economic losses. Knowledge of host preferences of these biting midges -especially of the relevant vectors of arboviruses near farms, such as Culicoides obsoletus in northern Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 77 publications
(118 reference statements)
1
10
0
Order By: Relevance
“…The ornithophilic species show a number of sensilla coeloconica ranging from eight to 13. The morphological sensillum types of antenna and host preference were not associated with their phylogenetic relationship ( Isberg, Hillbur & Ignell, 2013 ) but rather with volatile organic compounds, captured by different receptors present on sensillum types ( Zimmer et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ornithophilic species show a number of sensilla coeloconica ranging from eight to 13. The morphological sensillum types of antenna and host preference were not associated with their phylogenetic relationship ( Isberg, Hillbur & Ignell, 2013 ) but rather with volatile organic compounds, captured by different receptors present on sensillum types ( Zimmer et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Semiochemicals can provide information about the location, suitability, or physiological state of conspecifics, hosts, or breeding sites ( Logan & Birkett, 2007 ). Moreover, several studies carried out on feeding patterns of biting midges found variation in host attractiveness to be correlated with exhaled carbon dioxide (CO 2 ), 1-octen-3-ol, lactic acid, acetone ( Zimmer et al, 2015 ), specific phenolic compounds emitted from urine, ( Bhasin, Luntz & Mordue, 2001 ) or hair fragrance ( Mands, Kline & Blackwell, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…In case of domestic ruminants, SBV seroprevalence was also higher in cattle than in small ruminants (Larska et al, 2014a), which may be explained by the lower dose of SBV necessary to produce an infection in bovids comparing to sheep, which would need a 10-fold virus dose to seroconvert (Wernike et al, 2012;Poskin et al, 2014). Furthermore, larger hosts excrete more carbon dioxide and 1-octen-3-ol, the volatile attractants for haematophagous midges, which may increase the risk of the exposure to vector-borne pathogens (Koch and Axtell, 1979;Zimmer et al, 2015). As shown by Viennet et al (2013), midges prefer to feed on the largest hosts available in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Most probably, higher exposure in larger ruminants is associated with their higher production of carbon dioxide, one of the strongest attractants of many arthropods including Culicoides spp. [79,80]. SBV in utero infections may lead to congenital malformations of newborns, stillbirths, or abortions.…”
Section: Emerging Re-emerging and Vector-borne Pathogens Infecting mentioning
confidence: 99%